Community currency systems: Basic income, credit clearing, and reserve-backed. Models and design principles - Teodoro Criscione; Eve Guterman; Sowuelu Avanzo; Julio Linares (Albert-Ludwigs-Universität Freiburg, Freiburg Institute for Basic Income Studies (FRIBIS), 2022)
This paper briefly introduces models and basic design principles of community currency systems from economic and network analytical perspectives. Policymakers, grassroots organizations, and activists can find in this paper the necessary analytical and practical tools to start and enhance their own community currency projects.
Keywords: 330; community currency systems; complementary currency systems; basic income; monetary innovation; economic network analysis; circulation analysis; currency analysis; currency systems